HUBUNGAN KADAR NATRIUM DENGAN KADAR LDL (Low Density Lipoprotein) PADA LANSIA - Ekawati Sutikno; Hartati Tuna; Afi Bintan Syahadah (Cross-border, 2023)
Background: Elderly is someone who is >60 years old and identical with various drop status health, especially status health physique. Consumption of food with more sodium could increase pressure blood. Sodium t hat enters t he body will be directly absorbed into vessels blood. The thing this causes t h e rate of sodium in the blood to increase. Sodium nature withholds water, so that cause the volume of blood Becomes go on. LDL is called bad cholesterol because of its atherogenic effect (easily attached to the walls of blood vessels), so it can cause fat accumulation and narrowing of blood vessels (atherosclerosis). Objective: The aim of the study is for knowing the connection rate of sodium and LDL (Low-Density Lipoprotein ) in the elderly in RT 07 RW 08 Pojok Village, Mojoroto District Kediri City. Methods: The design of this study used a cross-sectional. The population is all elderly in the RT 07 RW 08 of Pojok Village, Mojoroto District, Kediri City, totaling 22 elderly. The research method used is Total Sampling. Analysis of the data used is Shapiro Wilk. Results: This study resulted in an average sodium level of ± 141.65 mmol/L and an average LDL level of 126.79 mg/dL. So there is no correlation between sodium and LDL levels with a p-value <0.05 (0.0191). Consultations and suggestions: This study concludes that there is no relationship between sodium and LDL levels in the elderly. Suggestions from this study are the elderly always maintain a healthy body by implementing a healthy lifestyle.